1990
DOI: 10.1159/000281720
|View full text |Cite
|
Sign up to set email alerts
|

Immune Status and Immune Therapy of Renal Cell Carcinoma

Abstract: At present, no sufficient therapy for metastatic renal cell carcinoma is available. Several immunotherapeutical protocols have been studied, success rates, however, were inconsistent. The purpose of this study was to assess the pretherapeutic immunological status of 13 patients with metastatic and 16 patients with nonmetastatic renal cell carcinoma and of 15 healthy volunteers. Determined were differential blood counts, lymphocyte subpopulations, β2-microglobulin, tumor necrosis factor (TNF), neopterin, immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…There are very few studies on serum TNFa and IL-1b in RCC patients. Bichler et al (1990) reported that when serum TNFa level was measured in 29 RCC patients, patients with metastatic disease could exhibit increased levels of serum TNF and that the decrease in TNF may be associated with a better prognosis. Dosquet et al (1997) reported that plasma TNFa level was higher in RCC patients compared to healthy controls, and that it was higher in the disseminated group compared to the undisseminated group.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few studies on serum TNFa and IL-1b in RCC patients. Bichler et al (1990) reported that when serum TNFa level was measured in 29 RCC patients, patients with metastatic disease could exhibit increased levels of serum TNF and that the decrease in TNF may be associated with a better prognosis. Dosquet et al (1997) reported that plasma TNFa level was higher in RCC patients compared to healthy controls, and that it was higher in the disseminated group compared to the undisseminated group.…”
Section: Discussionmentioning
confidence: 99%
“…Although RCC is infiltrated by numerous T cells, confirming that the immune system may control the growth of these tumors, this tumor model is also characterized by the existence of various immune defects that result in the global functional alteration of the cytotoxic T-effector cells. [32][33][34] It is known that human solid tumors mostly express tissue-specific antigens or self-antigens that may induce local tolerance, and cytotoxic T cells infiltrating RCC may correspond to antigenexperienced CTLs. In accordance with this hypothesis, we have previously shown that clonal KIR ϩ CTLs, bearing a memoryactivated phenotype, infiltrated RCC.…”
Section: Discussionmentioning
confidence: 99%
“…As described in more detail previously [6], leukocyte counts and differential blood counts (Technicon H I, Bayer Diagnostics, München, FRG) as well as lym phocyte subsets were assayed immediately after the blood samples had been taken. PBMC were harvested on Ficoll-Paque density gra dient (Pharmacia.…”
Section: Immunomonitoringmentioning
confidence: 99%
“…immunomonitoring must be regarded as an essential component of immunotherapy which allows optimization of therapy schedules by giving insight into the patients' individual immune system and the effect of immunotherapy. By means of monitoring cellular and humoral immune pa rameters of the peripheral blood during unspecific immunostimulalion in patients with metastatic RCC, we had found evidence of immunosuppression, which may im pair the immunostimulating effects of immunotherapy [6][7][8][9]. Immunosuppression in tumor patients can be me diated through different pathways ( fig.…”
Section: Introductionmentioning
confidence: 99%